Identification of an Evolutionarily Conserved Ankyrin Domain-Containing Protein, Caiap, Which Regulates Inflammasome-Dependent Resistance to Bacterial Infection - Tyrkalska, Sylwia D.; Candel, Sergio; Pérez-Oliva, Ana B.; Valera, Ana; Alcaraz-Pérez, Francisca; García-Moreno, Diana; Cayuela, María L.; Mulero, Victoriano (Frontiers in Immunology, 2017)
Many proteins contain tandemly repeated modules of several amino acids, which act as the building blocks that form the underlying architecture of a specific protein-binding interface. Among these motifs and one of the most frequently observed is ankyrin repeats (ANK), which consist of 33 amino acid residues that are highly conserved. ANK domains span a wide range of functions, including protein-protein interactions, such as the recruitment of substrate to the catalytic domain of an enzyme, or the assembly of stable multiprotein complexes. Here we report the identification of an evolutionarily conserved protein, that we term Caiap (from CARD- and ANK-containing Inflammasome Adaptor Protein), which has an N-terminal CARD domain and 16 C-terminal ANK domains and is required for the inflammasome-dependent resistance to Salmonella Typhimurium in zebrafish. Intriguingly, Caiap is highly conserved from cartilaginous fish to marsupials but is absent in placental mammals. Mechanistically, Caiap acts downstream flagellin and interacts with catalytic active Caspa, the functional homologue of mammalian caspase-1, through its ANK domain, while its CARD domain promotes its self-oligomerization. Our results therefore point to ANK domain-containing proteins as key inflammasome adaptors required for the stabilization of active caspase-1 in functionally stable, high molecular weight complexes.